Persepsi Peserta Didik Terhadap Pembelajaran Renang pada Kelas X SMA Negeri 1 Pare Tahun Pelajaran 2019/2020 - Nurlaila; Budi Hantoro (PT FORMOSA CENDEKIA GLOBAL, 2022)
This study aims to determine how big the students' perception of swimming lessons in class X SMA N 1 Pare in the 2019/2020 school year. This research is a quantitative descriptive research with survey method. The population in this study were students of class X SMA N 1 Pare totaling 190 students. The sampling technique used proportional random sampling technique. Validation of the data using the product moment formula with rhit > rtab (0.361) there are 28 valid questions. Data analysis was carried out by descriptive analysis. The research instrument uses a questionnaire. The results showed as many as 65 students or (50.39%) in the very positive category, as many as 61 students or (47.29%) in the positive category, as many as 3 students or (2.33%) in the less positive category and 0.00% in the negative category